Quantitative Evaluation of Tight Sandstone Reservoir Based on Diagenetic Facies—A Case of Lower Silurian Kepingtage Formation in Shuntuoguole Low Uplift, Tarim Basin, China - Li, Bin; Zhang, Hanbing; Xia, Qingsong; Peng, Jun; Guo, Qiang (Frontiers in Earth Science, 2021)
Tight sandstone reservoirs of Lower Silurian Kepingtage Formation are important exploratory targets for tight gas resources in the Shuntuoguole Low Uplift of Tarim Basin. How to evaluate tight sandstone reservoir is an urgent problem to be solved. In this study, we investigated the effects of diagenesis on the heterogeneity of tight sandstone deposits in similar sedimentary facies and established the relationship between the diagenetic facies and reservoir quality. Cores of tight sandstone reservoir of Lower Silurian Kepingtage Formation in Shuntuoguole Low Uplift are studied with thin section observation, SEM, XRD, and mercury injection. Quantification of diagenesis influencing porosity suggests that sandstone densification is mainly controlled by compaction, cementation, and hydrocarbon charging (bitumen charging), and the reservoir properties are effectively improved by dissolution, based on which 6 types of diagenetic facies are classified. Interpretation of the log data from individual wells with “K nearest neighbor (KNN)” algorithm concludes that top and base of S1k3-3 are believed to have favorably diagenetic reservoirs mainly falling in Type V; favorable diagenetic facies in S1k3-1 are dominantly Types V and VI which distribute irregularly; favorably diagenetic facies develop best in S1k1 predominated by Types V and VI which mainly distribute in its top. Composite analysis of diagenetic facies, sedimentary facies, and porosity distribution shows that the favorable area of further exploration and development is east of Well SH903 and north of Well SH10. This study may be able to be used as a useful reference for the reservoir quality evaluation and exploration of tight sandstone reservoirs for a similar area in the Tarim Basin.